Sociodemographic factors, level of physical activity and health-related quality of life in adults from the north-east of Sao Paulo, Brazil: a cross-sectional population study - Maciel, Nicoly Machado; Souza De Conti, Marta Helena; Penteado Simeao, Sandra Fiorelli Almeida; Dos Santos Genebra, Caio Vitor; Corrente, Jose Eduardo [UNESP]; De Vitta, Alberto (Bmj Publishing Group, 2018)
Objective To verify the association among sociodemographic variables, physical activity level and health-related quality of life in adults aged 20 years and over. Methods Population-based study, with household sample by clusters. The dependent variables were the PCS and MCS scores of the instrument 36-Item Short-Form Health Survey (SF-36), the independent variables were gathered in sociodemographic characteristics and the level of physical activity. Absolute and relative frequency distributions were used for categorical variables and bivariate analysis, using Student's West and ANOVA and multivariate using non-conditional logistic regression. Results Of the 600 interviewees, the mean PCS score for men was 80.2 and for women 74.6, while for MCS, 83.8 (+/- 16.9) and 76.5 (+/- 23.3), for men and women, respectively. Women tend to report lower scores than men in all domains: men (OR=4.83) and women (OR=4.80) were older (OR=4.34) (OR=3.57) and sedentary women (OR=1.90) were associated with lower PCS scores, while older men (OR=3.96) and widowed and separated' (OR=3.03) had lower MSC scores. Conclusion HRQoL was associated with advancing age and schooling, in both sexes, sedentary women and widowed and separated men.